COVID-19 and Child Vaccination: A Systematic Approach to Closing the Immunization Gap - Comfort Z. Olorunsaiye, PhD, MPH; Korede K. Yusuf, MBBS, MPH, PhD; Kylie Reinhart, BSPH; Hamisu M. Salihu, MD, PhD (Global Health and Education Projects, Inc., 2020)
The COVID-19 pandemic threatens to set back major successes that have been achieved in global vaccine initiatives. We conducted a rapid review and synthesis of the literature on immunization provision and Utilization since the onset of the COVID-19 pandemic. A total of 11 papers comprising peer-reviewed articles and key policies and guidelines, published between January 1 and June 15, 2020, were analyzed. Widespread disruptions of routine immunization and vaccination campaigns were reported leaving millions of children worldwide at risk of measles outbreaks. We present an expanded model of the World Health Organization's Global Routine Immunization Strategic Plan (GRISP) action areas as a tool to help countries quickly adapt to immunization challenges in the presence of COVID-19 and close the emerging immunization coverage gaps. Key words: • Immunization • Child health • Vaccination • COVID-19 • Essential health services • Corona virus   Copyright © 2020 Olorunsaiye et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.